STRATEGI PENGEMBANGAN USAHA MELALUI MEDIA SOSIAL PADA UKM ABANG’S DAGING SANGATTA - Rizky Aulia Hidayah (Sekolah Tinggi Ilmu Ekonomi Nusantara Sangatta, 2021)
The purpose of this study was to find out how the business development strategy of Abang's Meat Sangatta in developing its business. So that Abang's Meat Sangatta can determine strategies that can be used by business owners in the face of intense competition. One way that can be done to help determine a business development strategy is to conduct a SWOT analysis to determine the strengths, weaknesses, opportunities, and threats. Based on the results of the analysis conducted by researchers, Abang's Meat Sangatta is in quadrant I, namely by supporting the S-O aggression strategy in the SWOT matrix, where the business development strategy used is to maintain product quality, improve operational tools to maintain product quality to be offered to new consumers, improve marketing through social media in order to expand market reach so that products can be known more widely.